Geometric morphometrics species discrimination within the Genus Nemipterus from Malaysia and its surrounding seas - AYESHA IMTIAZ; DARLINA MD NAIM (Biodiversitas Journal of Biological Diversity, 2018)
Imtiaz A, Md Naim D. 2018. Geometric morphometrics species discrimination within the Genus Nemipterus from Malaysia and its surrounding seas. Biodiversitas 19: 2316-2322. High demand of fish protein diet and exposure of marine fish to a challenging marine environment has increased the importance of advanced fisheries research especially in Malaysian waters, particularly research related to taxonomy, biology, diversity, population structure as well as phylogenetic histories of commercially important marine fish species to ensure continuous supply of fish and fish products. This current research aimed to explore the potential of geometric morphometrics method to discriminate among taxa of genus Nemipterus through body size and shape differences. A total of 171 individuals representing ten species of genus Nemipterus collected from Malaysia and its surrounding seas were examined. The resulting homologous landmarks were subjected to generalized procustes analysis followed by principal component analysis. Principle component scores were further investigated to cross-validated discriminant analysis to determine the efficacy of landmarks in discriminating by taxon. Our finding shows that species within the genus Nemipterus can be differentiated using geometric morphometrics method as strongly depicted by canonical variance analysis. This current study is the first report utilizing geometric morphometrics approach conducted on the genus Nemipterus from Malaysian waters.